La Doctrina del Shock. El auge del capitalismo del desastre - Lange Valdés, Carlos (Revista INVI, 2010)
Naomi Klein. Paidós Ediciones, 2010, 701 pp. [Toronto: A.Knopf Ed., 2007]. ISBN 978-84-493-2345-4.